New Approaches of Preparing the Population for Correct Actions During Earthquakes Using Innovative Technologies - Galimova Liliya Gazisovna; Gennadievna, Kim Svetlana (European Journal of Life Safety and Stability (2660-9630), 2022)
This article discusses new approaches in the field of preparing all segments of the population for the right actions when receiving a forecast and during earthquakes using innovative technologies.